Penerapan Teknik Kursi Kosong dalam Mereduksi Toxic Relationship ( Studi Kasus Klien "P") - Sari Utami; Abdur Razzaq; Lena Marianti (Journal of Society Counseling, 2024)
This research is entitled Application of the Empty Chair Technique in Reducing Toxic Relationships (Case Study of Client "P" at the Ar-Rahman Drug Rehabilitation Center Foundation). A person experiencing a toxic relationship can be seen from excessive suspicion, likes to bring up mistakes, is always looked down upon with all his shortcomings, has poor communication, has a feeling of not wanting to be defeated, is always used as an outlet for anger, there are threats and relationships. The aim of this research is first, to find out the description of the toxic relationship of client "P' at the Ar-Rahman Drug Rehabilitation Center Foundation. Second, to find out the application of the empty chair technique in reducing toxic relations with client "P" at the Ar-Rahman Drug Rehabilitation Center Foundation. In this research, the author used field research, a qualitative approach, and used a case study research method. The subject of this research is client "P'. The tools for collecting data in this research are observation, interviews and documentation. Research results, 1) client "P''s household is classified as a toxic relationship. Where "P" clients often feel excessively suspicious, always bring up their partner's mistakes, don't want to be defeated, have poor communication, always vent their anger at their partner, there are threats in the relationship. 2) The application of the empty chair technique consists of 3 stages. Initial stage, implementation stage and termination stage. The results of applying the empty chair technique enable client "P" to build a good relationship with their partner.